Mobility, Poverty, and Gender: Travel 'Choices' of Slum Residents in Nairobi, Kenya - Salon, D. (2012)
A survey of 4375 slum residents in Nairobi, Kenya, reveals that the majority cannot afford any of the motorized transport options in the city. They cope by limiting their travel outside their settlement and, if they do travel, by often 'choosing' to walk. As compared to the non-poor, poor households are systematically worse off. But the burden of reduced mobility is borne disproportionately by women and children. Using joint-choice modelling to empirically explore the travel 'choices' of Nairobi's slum residents, we show that women, men, and children in this population face distinct barriers to access. We conclude that policy aiming to improve mobility and transport access for the poor needs to grapple not only with the crucial issue of affordability but also with specific constraints faced by women and children.